LIN28B expression is downregulated in mature spermatozoa of oligozoospermic men and associates with genetic variants previously linked to pubertal onset - María Cecilia Lardone; Marina Díaz-Fontdevila; Eliana Ortiz; Germán Iñiguez; Pamela Inostroza; Cristóbal Espinoza; Mauricio Ebensperger; Kristian Almstrup; Andrea Castro (Endocrine Connections)
LIN28B is an RNA-binding protein that acts as a post-transcriptional regulator of genes involved in developmental timing and self-renewal through its interaction with let-7 miRNAs. Large-scale genomic studies have strongly implicated SNPs in LIN28B with male puberty timing. In addition, the occurrence of late puberty is linked to diminished semen quality in adult life. Therefore, we aimed to study the association of puberty-linked LIN28B genetic variants with semen parameters, reproductive hormones and the spermatozoa expression of the LIN28B/Let-7 axis in idiopathic oligozoospermic men. One hundred and eleven oligozoospermic (cases) and 258 men with normal sperm concentration (controls) were genotyped for five LIN28B SNPs (rs7759938, rs395962, rs314268, rs314277 and rs314280). The abundance of the LIN28B transcript, let-7a and let-7c miRNAs were measured by qRT-PCR in RNA isolated from purified sperm. Serum blood samples were analysed for reproductive hormones. Lower abundance of the LIN28B transcript and higher expression of let-7c were observed in cases (P < 0.001). Furthermore, rs395962_T was associated with a reduced abundance of the LIN28B transcript in cases (dominant: P = 0.032). On the other side, we observed a positive association of rs314277_A (Additive: P = 0.024), rs7759938_C (dominant: P = 0.025) and rs314280_A (dominant: P = 0.024) with total testosterone levels in cases. The decreased transcript abundance of LIN28B in sperm of idiopathic oligozoospermic men and its association with SNPs known to affect the onset of puberty and total testosterone levels suggests a role for LIN28B in the primary impairment of spermatogenesis through its expression in early germ cells or regulating the testicular biosynthesis of testosterone at a central level. Therefore, our results provide a potential mechanistic link between the regulation of pubertal timing and adult testicular function.